2016
DOI: 10.1039/c6ee00383d
|View full text |Cite
|
Sign up to set email alerts
|

CO2 photo-reduction: insights into CO2 activation and reaction on surfaces of photocatalysts

Abstract: This review describes the current understanding of CO2 photoreduction on the surface of heterogeneous catalysts with a particular focus on the reaction mechanism and pathways as well as the adsorption/activation of CO2.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
987
0
20

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 1,631 publications
(1,066 citation statements)
references
References 142 publications
(157 reference statements)
5
987
0
20
Order By: Relevance
“…It was proposed that CO 2 chemisorbed on catalysts with three structures (Figure 14e): (1) oxygen coordination structure with oxygen donating electrons to surface Lewis acid centers; (2) Carbon coordination structure with carbon gaining electrons from Lewis base centers; (3) Mixed coordination structure with carbon gaining electrons and oxygen donating electrons. [107] The chemisorption of CO 2 δ − changed CO 2 geometry from linear structure to a bent form, which featured a lower barrier for accepting an electron since the LUMO level decreased as the molecule bended.…”
Section: Interactions With Reactantsmentioning
confidence: 99%
“…It was proposed that CO 2 chemisorbed on catalysts with three structures (Figure 14e): (1) oxygen coordination structure with oxygen donating electrons to surface Lewis acid centers; (2) Carbon coordination structure with carbon gaining electrons from Lewis base centers; (3) Mixed coordination structure with carbon gaining electrons and oxygen donating electrons. [107] The chemisorption of CO 2 δ − changed CO 2 geometry from linear structure to a bent form, which featured a lower barrier for accepting an electron since the LUMO level decreased as the molecule bended.…”
Section: Interactions With Reactantsmentioning
confidence: 99%
“…Despite the tremendous achievements, direct CO 2 photo-reduction is still believed to be challenging because CO 2 molecule has a stable thermodynamic configuration and a high energy barrier impeding its activation and conversion. Meanwhile, the reaction processes are multistep and complicated, indicating the difficulty of maneuvering the products [15]. For this reason, their conversion efficiency and selectivity are largely limited.…”
Section: Introductionmentioning
confidence: 99%
“…Tremendous efforts have been focused on photoelectrochemical (PEC) [7][8][9] and photocatalytic water splitting [10][11][12] for maximizing the utilization efficiency of solar energy, which generally employs semiconductors as light-harvesting antennas. Considering the excessive emission of atmospheric carbon dioxide (CO 2 ) caused by the combustion of fossil fuels, the sunlight-driven CO 2 reduction into higher energy chemicals, such as carbon monoxide, formic acid, methanol or methane, offers a more promising approach to alleviate both global warming and energy crisis [13][14][15][16][17]. Since the pioneering research for photocatalytic CO 2 reduction using a series of semiconductor powders in water was reported in 1979 [18], the development of photocatalysts for CO 2 reduction has been explored with great efforts.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly to the electric current being the driving force of the process, it has been proposed that the charge redistribution upon the photoactivation can also lead to the activity of supported non-noble metal clusters in the CO 2 reduction [15]. Numerous semiconductors have been studied in such a reaction, even as early as 1979 [16] but even after relatively long time of research, currently reported activity of supported Cu is still relatively small [17].…”
Section: Introductionmentioning
confidence: 99%